PENGARUH TRANSAKSI INVESTOR ASING TERHADAP TRANSAKSI INVESTOR DOMESTIK DI PASAR MODAL INDONESIA - Astikawati, Yunita; Relita, Dessy Triana (STKIP Persada Khatulistiwa Sintang, 2017)
Abstract: This study aimed at exploring the influence of investment decisions of foreign investors to domestic investors. Investment decisions measured based on volume and frequency of share trading in the Indonesian share market. The data of the research obtained from the transaction data on 2011-2015. Furthermore, the data analyzed using regression analysis. The finding of the data analysis showed that the foreign investor trading activities has a significant and positive impact on domestic investor trading activities. Based on the lag found that the trading transaction of foreign investor was not significantly affected the domestic investor trading activities. Therefore it could be concluded that foreign investors become a reference for domestic investors in making investment decisions in the current year but not a reference for the following year due to the future economic movement which is influenced by other factors that could not be predicted.Keywords: Transactions, Foreign And Domestic Investors, Capital MarketsAbstrak: Penelitian ini mengekspolasi pengaruh keputusan investasi investor asing terhadap investor domestik. Keputusan investasi diukur menggunakan volume dan frekuensi perdagangan saham di pasar modal Indonesia. Penelitian ini menggunakan data transaksi dari tahun 2011-2015. Data penelitian ini dianalisis menggunakan analasis regresi. Hasil analisis data menunjukan bahwa aktivitas jual beli saham investor asing di pasar modal indonesia berpengaruh signifikan dan positif terhadap aktivitas jual beli saham investor domestik. Secara lag ditemukan transaksi jual beli saham investor asing tidak signifikanÂ terhadap transaksi jual beli saham investor domestik. Oleh karena itu disimpulkan bahwa investor asing menjadi acuan bagi investor domestik dalam membuat keputusan investasi pada tahun berjalan namun tidak menjadi acuan untuk tahun berikutnya. Hal ini dikarenakan pergerakan ekonomi di masa mendatang dipengaruhi faktor lain-lain yang belum dapat diprediksi kepastiannya.Kata Kunci: Transaksi, Investor Asing Dan Domestik, Pasar Modal